Time Spreads in China SSE 50 Options - Slivka, Ronald T.; Wang, Ruichen (Indian Journal of Research in Capital Markets, 2019)
Using day-end pricing data from a comprehensive database not readily available outside of China, an algorithm to trade near-the-money call option time spreads on China’s SSE 50 ETF was developed and tested. Analysis of in-sample data suggested profitable trading rules that, when applied to limited out-of-sample data, failed to produce superior similar results. A likely explanation for this was offered and further testing was planned. To our knowledge, there are no known related studies of SSE 50 option time spreads; so, this work provides a helpful addition to the growing knowledge about the developing China market.